Implementasi Aplikasi Konferensi Video Berbasis WebRTC dengan Fitur Berbagi dan Rekam Layar - Beny Rahman Hakim; Abdullah Ardi; Budi Styawan; Yazid Aufar (Bulletin of Information Technology (BIT), 2023)
Video conference is now commonly used in a variety of daily activities. There are many applications available to perform it, but most of these platforms require users to subscribe so that all features can be fully utilized. Web Real-Time Communication (WebRTC) is a framework that functions to establish a real-time communication over the internet. This technology works in a peer-to-peer basis and can be implemented in building low-cost video conference application without worriying about feature limitations. Screen sharing and recording facilities, which are restricted in most applications, can easily be accommodated by WebRTC. This research aims to build a video conference application based on WebRTC framework that is capable of sharing and recording screen during meeting. Additionally, some useful features are also added, such as microphone/camera control, displaying user names, counting the number of participants, sending text messages and sharing files. System development refers to waterfall method, which starts from analysis to testing steps. The language used for implementing the system include HTML, JavaScript, CSS and some Node.js libraries. After that, the application is deployed on a hosting server to make it accessible on the internet. The result of black box testing method shows that all features can run normally without problem. In addition, it is also known that the application is able to connect up to 13 people in the same meeting